Aktivitas Fisik dan Risiko PPOK pada Pengemudi Becak di Surabaya: Physical Activities and COPD Risks in Pedicab Drivers in Surabaya - Amelia Lorensia; Rivan Virlando Suryadinata; Noer Lailatul Istiqomah; I Nyoman Yoga Diputra (Jurnal Sains dan Kesehatan, 2021)
Pedicab drivers have low economic level and smoking is a social habit that very risk of experiencing lung function disorders, but are also classified as having routine physical activity while pedaling the rickshaw. The purpose was to determine physical activity and risk of COPD from the value of lung function in pedicab drivers in Surabaya. The research design was cross-sectional research in March-December 2018. The location used was in the vicinity of the Surabaya area. The research variables included: pulmonary function disorders by measuring spirometry and physical activity using the International Physical Activity Questionnaire (IPAQ). The data analysis was descriptive. The total respondents were men, amounting to 188 people. Most of the respondents had moderate lung function disorders at 82.45%. Respondents with impaired lung function had high physical activity profile of 1 person (0.61%); moderate physical activity profile was 155 people (95.09%) and and low physical activity profile was 7 people or 4.29%. Respondents with non-impaired lung function have a moderate physical activity profile of 25 people (100%). Therefore, it was necessary to further research the factors that can affect the decline in lung function of pedicab drivers in addition to physical activity.